1990
DOI: 10.1515/bchm3.1990.371.1.117
|View full text |Cite
|
Sign up to set email alerts
|

Potential Proteolytic Activity of Human Plasma Fibronectin: Fibronectin Gelatinase

Abstract: Human plasma fibronectin contains a latent proteinase that after activation cleaves gelatin and fibronectin. The autoactivation propensity of the two purified cathepsin D-produced fragments of fibronectin (190 and 120 kDa) was compared. Both polypeptides were spontaneously activated in the presence of Ca 2 ®. This activation was inhibited by EDTA. The active gelatinase was isolated from the autodigest of the 190-kDa fragment. Among various protein substrates, including laminin and native type I and IVcollagens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
1

Year Published

1991
1991
2005
2005

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 21 publications
1
14
0
1
Order By: Relevance
“…For instance, some Fn fragments exhibit catalytic activities. 5,7,[18][19][20][21][22] This is the case for the GBD, which displays zinc-dependent collagenase/gelatinase activity, 5,6 called Fn-proteinase. 4 We hypothesized that these cryptic activities of Fn domains may also arise from alternative splicing.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, some Fn fragments exhibit catalytic activities. 5,7,[18][19][20][21][22] This is the case for the GBD, which displays zinc-dependent collagenase/gelatinase activity, 5,6 called Fn-proteinase. 4 We hypothesized that these cryptic activities of Fn domains may also arise from alternative splicing.…”
Section: Discussionmentioning
confidence: 99%
“…Other fragments stimulate the expression of matrix metalloproteinases, tumor necrosis factor-a, tissue inhibitor of metalloproteinase 1 and urokinase type plasminogen activator [107][108][109]. Finally, several studies reported the existence of four different cryptic proteinases (as their physiological relevance is unknown as well as their proteolytic mechanism) in human pFN, designated as fibronectinase (a serine protease), FN-gelatinase and FN-lamininase (aspartic proteases) and FN-type IV collagenase (a metalloprotease) [110][111][112][113]. It is, however, noteworthy that the four enzymes in fibronectin, which we will next address in detail, need further characterization in order to unequivocally demonstrate their existence.…”
Section: Fibronectin: Four Proteinases Within a Single Proteinmentioning
confidence: 99%
“…In addition to Fnase, human plasma fibronectin has been described as containing two additional latent aspartic proteinases, 111], similarly to retroviral aspartic proteinases.…”
Section: Fibronectin-gelatinase and Fibronectin-lamininasementioning
confidence: 99%
See 2 more Smart Citations